Association of patient weight status with plasma surfactant protein D, a biomarker of alveolar epithelial injury, in children with acute respiratory failure. Issue 10 (7th August 2020) - Ward, Shan L.; Dahmer, Mary K.; Weeks, Heidi M.; Sapru, Anil; Quasney, Michael W.; Curley, Martha A. Q.; Liu, Kathleen D.; Matthay, Michael A.; Flori, Heidi R.
Abstract: Aims and Objectives: Alveolar epithelial injury is a key determinant of acute respiratory failure (ARF) severity. Plasma surfactant protein D (SP‐D), a biomarker of alveolar epithelial injury, is lower in obese adults with ARF compared to their lean peers. We aimed to determine if children with ARF have similar variance in plasma SP‐D associated with their weight status on admission. Methods: Plasma SP‐D was measured on days 0, 1, or 2 in children (1‐18 years) with ARF enrolled in the genetic variation and biomarkers in children with acute lung injury and RESTORE studies. Weight classification (underweight, normal, overweight, and obese) was based on body mass index or weight‐for‐height z‐scores. Associations between weight group and SP‐D on each day were tested. Results: Inclusion criteria were met in 212 subjects, 24% were obese. There were no differences among weight groups in SP‐D levels on days 0 and 1. However, on day 2, there was a statistically significant linear trend for lower SP‐D levels as weight increased in both the univariate analysis ( P  = .02) and when adjusting for age, ethnicity, and diagnosis of pediatric acute respiratory distress syndrome ( P  = .05). Conclusions: Obesity was associated with lower plasma SP‐D levels on day 2 of ARF. This finding may be explained by altered ARF pathogenesis in obese individuals or a reduced incidence of ventilator‐induced lung injury.